Social disparities in the prevalence of diabetes in Australia and in the development of end stage renal disease due to diabetes for Aboriginal and Torres Strait Islanders in Australia and Maori and Pacific Islanders in New Zealand - Kathleen Hill; Paul Ward; Blair S. Grace; Jonathan Gleadle (BMC, 2017)
Abstract Background Disparities in health status occur between people with differing socioeconomic status and disadvantaged groups usually have the highest risk exposure and the worst health outcome. We sought to examine the social disparities in the population prevalence of diabetes and in the development of treated end stage renal disease due to type 1 diabetes which has not previously been studied in Australia and New Zealand in isolation from type 2 diabetes. Methods This observational study examined the population prevalence of diabetes in a sample of the Australian population (7,434,492) using data from the National Diabetes Services Scheme and of treated end stage renal disease due to diabetes using data from the Australian and New Zealand Dialysis and Transplant Registry. The data were then correlated with the Australian Bureau of Statistics Socioeconomic Indexes for Areas for an examination of socioeconomic disparities. Results There is a social gradient in the prevalence of diabetes in Australia with disease incidence decreasing incrementally with increasing affluence (Spearman's rho = .765 p < 0.001). There is a higher risk of developing end stage renal disease due to type 1 diabetes for males with low socioeconomic status (RR 1.20; CI 1.002-1.459) in comparison to females with low socioeconomic status. In Australia and New Zealand Aboriginal and Torres Strait Islanders, Maori and Pacific Islanders appear to have a low risk of end stage renal disease due to type 1 diabetes but continue to carry a vastly disproportionate burden of end stage renal disease due to type 2 diabetes (RR 6.57 CI 6.04-7.14 & 6.48 CI 6.02-6.97 respectively p < 0.001) in comparison to other Australian and New Zealanders. Conclusion Whilst low socioeconomic status is associated with a higher prevalence of diabetes the inverse social gradient seen in this study has not previously been reported. The social disparity seen in relation to treated end stage renal disease due to type 2 diabetes for Aboriginal and Torres Strait Islanders, Maori and Pacific Islanders has changed very little in the past 20 years. Addressing the increasing incidence of diabetes in Australia requires consideration of the underlying social determinants of health.